Istiḥsān and Judicial Recalibration of Marital Property Rights in Indonesia's Religious Courts - Darmawan; Nur Lailatul Musyafaah; Mohammad Ikhwanuddin; Muhammad Syafiq Mughni (AHKAM : Jurnal Ilmu Syariah, 2026)
This study analyzes the evolution of marital property division (harta bersama) jurisprudence in Indonesia’s Religious Courts through the lens of istiḥsān as a method of Islamic legal reasoning (uṣūl al-fiqh). Traditionally, courts applied a rigid 50:50 division upon divorce or death, grounded in the Compilation of Islamic Law and Law No. 1 of 1974. Recent Supreme Court cassation decisions, however, demonstrate a shift toward proportionate division while maintaining doctrinal coherence. Using doctrinal analysis and a structured synthesis of three leading decisions, this study identifies three jurisprudential patterns: 1) reaffirmation of equal division when deviation is unjustified; 2) calibrated adjustment based on economic contribution, unpaid domestic labor, maintenance failure, and childcare responsibilities; and 3) proper sequencing in death cases by allocating marital property before distributing the estate through inheritance. These rulings operationalize istiḥsān within the maqāṣid al-sharīʿah framework to achieve substantive justice where formal equality undermines fairness. The study proposes a practical framework to enhance consistency, gender justice, and legal certainty in future adjudication.   Abstrak Penelitian ini menganalisis perkembangan yurisprudensi pembagian harta bersama di Pengadilan Agama Indonesia melalui pendekatan istiḥsān sebagai metode penalaran hukum Islam (uṣūl al-fiqh). Selama ini, pengadilan cenderung menerapkan pembagian kaku 50:50 dalam perkara perceraian maupun kematian, sebagaimana diatur dalam Kompilasi Hukum Islam dan Undang-Undang Nomor 1 Tahun 1974. Namun, sejumlah putusan kasasi Mahkamah Agung terbaru menunjukkan pergeseran menuju pembagian proporsional tanpa meninggalkan konsistensi doktrinal. Melalui analisis doktrinal dan sintesis terstruktur terhadap tiga putusan kunci, penelitian ini mengidentifikasi tiga pola utama: 1) penguatan pembagian setara ketika tidak terdapat alasan pembeda; 2) penyesuaian proporsional berdasarkan kontribusi ekonomi, kerja domestik tidak berbayar; 3) kegagalan nafkah, dan beban pengasuhan anak; 3) serta penegasan urutan hukum dalam perkara kematian dengan memisahkan harta bersama sebelum pembagian waris. Pendekatan ini menempatkan istiḥsān dalam kerangka maqāṣid al-sharīʿah untuk mewujudkan keadilan substantif, kepastian hukum, dan keadilan gender.